Evaluation of crystal structure in TlInS2 by optical second- harmonic generation. (May 2015) - Wakita, K; Hagiwara, M; Paucar, R; Shim, Y; Mimura, K; Mamedov, N
Abstract: Second-harmonic generation (SHG) in layered TlInS2 crystals was studied over the temperature range of 77-300 K using a confocal laser microscope system. As expected, the SHG signal was observed in the low temperature ferroelectric phase of the layered compound. In addition, the polarization properties of the SHG signals of TlInS2 were investigated in the 80-180 K range. The results are in good agreement with those of the symmetric space group C 3 2 in the ferroelectric phase.